Kewenangan Inspektorat Daerah dalam Menindak Pejabat Atas Penyimpangan Administratif Keuangan - Rendra Setiyo Perman; Ali Akbar Rafsanjaya; Lia Febrianti; Aisha Nurhayati Istitaah (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
This study aims to determine the form of legal modification of the authority of the district/city regional inspectorate in preventing criminal acts of corruption in the district/city regional government. The research method used is normative legal research. The results of the study indicate that the authority of the District/City Regional Inspectorate as regulated in several laws and regulations urgently needs to be modified to strengthen the authority of the District/City Inspectorate in preventing criminal acts of corruption in the District/City Regional Government. The modification in question is carried out in the form of revision/change of laws and regulations, where currently the position of the District/City Inspectorate is still parallel to the Regional Apparatus Organization, in the future it will be parallel to the Regional Secretary. The second modification is carried out in the form of repositioning the Role/Duties of the District/City Regional Inspectorate by encouraging the realization of Good Governance and Clean Government, Developing Supervisory Synergy, Supporting Efforts to Eradicate Corruption, Optimizing the Increase in State Revenue, Playing a Role in the Implementation of Regional Autonomy. While the third modification that can be done is through Institutional Development through the development of structures, Work Procedures, and Human Resources.